Gelora Reformasi dari Masjid Gedhe Kauman: Aksi Pertama Luar Kampus di Yogyakarta Jelang Lengsernya Presiden Soeharto, 21 Mei 1998 - Ghifari Yuristiadhi (Lembaran Sejarah, 2013)
This paper attempts to present an event prior to the fall of President Suharto in May 21 1998 in Yogyakarta. Studies that preceded this paper highlighted the dynamics in Jakarta, as the capital of the country. Even then, most of the studies highlighted Semanggi tragedy or some previous events that occurred approximately 1-2 weeks prior to his resignation, especially on campus. This paper presents community of Yogyakarta demonstration at the Great Mosque of Kauman Yogyakarta which is the frst ‘off-campus action’ in Yogyakarta before fall of Suharto. This paper presented by historical method utilizing secondary sources such as newspapers and books, and interviews.